The Discrepancy of Meaning: A Study of a Guardian Angel’s Existence in “Deus Ex Machina” - Harfiyah Widiawati; Aris Masruri Harahap; Lambok Hermanto Sihombing (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
The theme of a guardian angel has always become cryptic discussion among scholars, for as God, she is beyond our empirical grasp. Hari Kunzru is one of the writers who broach this subject in his work entitled “Deus Ex Machina”. In the short story, the guardian angel acts as the I-character of the story as well as the I-narrator of the story. By using theories on textual deconstruction and existentialism, we discuss and analyze the guardian angel’s raison d’etre (reason to be) and significance through her functions as the narrator and also the I-character in the narration of “Deus Ex Machina” story. From the analysis, we could draw three conclusions which relate raison d’etre (reason to be) and the significance of the guardian angel with the other characters within the story and with her readers outside the story.